Activating students’ cognitive perspective using problem based learning in Efl speaking class - Nurvia Silviana; Fauzi Miftakh (Politeknik Negeri Bali, 2021)
Speaking is one of the skills in mastering English that must be taught and learned in senior high school. The problem based learning (PBL) is an appropriate strategy to assist the students in their speaking skills learning. Cognitive perspective also takes accountability on this research due to students’ perspective toward the PBL that moreover influences their speaking skills. The purpose of the research is to explore students’ perception about problem based learning also to discover the phase in PBL that delivers students’ cognitive aspect in the speaking classroom at the second year students of SMAN 1 Karawang. Qualitative research was used as the research approach with descriptive research as the method of this research. This research took place at SMAN 1 Karawang by taking the XI IPA 5 class as the sample with six research participants. They were chosen by purposive sampling. All of the data was gathered through observation, student’s reflection journals, and documentation. It was found that the use of PBL technique was able to assist the constraints of students in solving a problem along the way with their cognitive perspective while speaking it out. Moreover, the researcher also discovers that PBL and cognitive perspective hold strong intercourse between each other, the phase in PBL goes along with human mental processes particularly in cognitive views. Furthermore, it shows how PBL assists students in their problem-solving skills with their cognitive views and how it triggered them so they can elaborate on it in front of the class. PBL and speaking activity were two items that always go right together.